Ação da Euphorbia tirucalli L. na formação de focos de cripta aberrante na mucosa cólica induzida por azoximetano em ratos - Andrade, Denise de Albuquerque (2007)
Colorectal cancer is the fifth most frequently diagnosed malignancy in Brazil. The etiology may be related with inherited and life-style that can be modified. Aberrant crypt foci have been recognized as early preneoplastic lesions and being related with colorectal adenoma and precursors of cancer in humans. Undertanding the nature of early appearing lesions efforts to find effective agents in colorrectal cancer. The aim of this study was verify the potential chemopreventive of aqueous solution of the latex of Euphorbia tirucalli L. in aberrant crypt foci (ACF) in rats induced with azoxymethane (AOM). Thirty-two Wistar male rats were used, average weight 100g -200g (4 - 6 weeks). They were randomly divided into 04 groups of 08 animals each. Group 01 with rats induced with AOM and treated with aqueous extract of the latex of E. tirucalli L., group 02 with rats induced with AOM without treatment with aqueous extract of the latex of E. tirucalli L., group 03 with rats without AOM induction and treated with aqueous extract of the latex of E. tirucalli L. and group 04 with rats without induction with AOM and without treatment with aqueous extract of the latex of E. tirucalli L.. The animals of the groups 01 and 02 were injected intraperitoneallly (IP), with AOM once a weekly for 02 weeks at a dose level of 12 mg/kg body weight. One week before the beginning of the administration of the carcinogen, it was administered solution daily by intragastric gavage, respectively, aqueous extract of latex of E. tirucalli L. 400mg/Kg and physiologic solution to 0,9%. The groups 03 and 04 were not induced with AOM and they received daily solution by gavage, respectively, aqueous extract of the latex of E. tirucalli L. 400mg/Kg and physiologic solution to 0,9%. All groups continued receiving daily solutions by intragastric gavage until the day established for euthanasia. All animals were sacrificed by diethyl ether inhalation 15th week, after AOM initiation or sterile solution injected IP. The animals were evaluated concerning to the weight, clinical alteration, presence of adenomas or colic tumors, and the presence of ACF and the number of crypts for each focus (multiplicity) in agreement with colic location, defined area distal, medial and proximal. We verified in the present study that the aqueous extract of E. tirucalli L. (400mg/kg) presented a significant decrease of the global number of ACF group 01 compared to the group 02 (p<0,001). Additionally, the multiplicity in these groups showed significant decrease (p<0,0001) in the number of ACF with 5 crypts/focus in the whole large intestine. This study suggests the aqueous extract of E. tirucalli L. has potential chemopreventive against colon carcinogenesis with inhibition of the formation of ACF in rats induced with AOM .